Management assessment of superficial venous thrombophlebitis in lower limb - الحسين, احمد; حسام كنجو (Latakia University Journal -Medical Sciences Series, 2024)
Background: Optimal doses and duration of anticoagulants or non‐steroidal anti‐inflammatory drugs (NSAIDs) for the treatment of superficial vein thrombosis (SVT) are still uncertain. Objectives: To compare the efficacy and safety of therapuetic dose of rivaroxaban, prophylactic dose of rivaroxaban and oral non-steroidal anti-inflammatory drugs (Etorecoxib) for acute lower limb SVT. Patients and methods: Inpatients and Outpatients with at least a 5-cm-long acute SVT of long or short saphenous veins or their collaterals were randomized to receive rivaroxaban either 10 mg once daily for a mounth (group A) or 20 mg once daily for a mounth (group B) or 90 mg etorecoxib once daily for a mounth (group C), in a double-blind fashion. The main outcome measure was to compare the rate of recurrence or extension of SVT (symptomatic and asymptomatic), DVT (symptomatic and asymptomatic), PE (symptomatic) and reduction in pain during a 3-month follow-up period. The main safety measure was death or major hemorrhage. Results: Among 76 patients, the main complications occurred in 3/24 (12.5%), 4/27 (14.8%) and 4/25 (16%) subjects in groups (group A), (group B) and (group C), respectively. (group A) vs. (group B): P>0.05; (group A) or (group B) vs. (group C): P<0.05. During the 3-month follow-up period, the event rate was similar in all groups. No death or major hemorrhage occurred during the study. Conclusions: A therapuetic dose or prophylactic dose of rivaroxaban is superior to oral non-steroidal anti-inflammatory drugs (Etorecoxib) for acute lower limb SVT during a mounth treatment period with similar results for a 3-month follow-up period.